Microeconomic approaches to development: Schooling, learning, and growth - Mark R. Rosenzweig (Yale University, Economic Growth Center, 2010)
I illustrate the variety of approaches to development issues microeconomists employ, focusing on studies that illuminate and quantify the major mechanisms posited by growth theorists who highlight the role of education in fostering growth. I begin with a basic issue: what are the returns to schooling? I discuss microeconomic studies that estimate schooling returns using alternative approaches to estimating wage equations, which require assumptions that are unlikely to be met in low-income countries, looking at inferences based on how education interacts with policy and technological changes in the labor and marriage markets. I then review research addressing whether schooling facilitates learning, or merely imparts knowledge, and whether there is social learning that gives rise to educational externalities. I next examine studies quantifying the responsiveness of educational investments to changes in schooling returns and assess whether and where there exist important barriers to such investments when returns justify their increase.
Keywords: O11; O15; O33; J24; 330; schooling; development; growth; Entwicklungstheorie; Bildungsökonomik; Bildungsertrag; Lernen; Soziale Beziehungen